Detection of Adolescent Tuberculosis in Uzbekistan Region (Czech Journal of Multidisciplinary Innovations, 2023)
This article aims to delve into the detection of adolescent TB in Uzbekistan, highlighting the challenges, opportunities, and potential strategies for improving case identification and management. By understanding the unique aspects of adolescent TB, healthcare professionals, policymakers, and stakeholders can develop targeted interventions to combat this silent epidemic effectively.